AKUNTABILITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBD) DALAM PENYELENGARAAN PEMERINTAHAN DESA DI DESA KASUKIA KECAMATAN WONGGEDUKU BARAT KABUPATEN KONAWE TAHUN ANGGARAN 2021 - Yuliana Musin; Waesti Nawawula (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
Accountability of the Management of the Village Revenue and Expenditure Budget (APBD) in the Implementation of Village Government, In Kasukia Village, West Wonggeduku District, Konawe Regency. This study describes how the accountability of the management of the village income and expenditure budget (APBD) in the implementation of village government is in the village of Kasukia. The data collection techniques used interview, observation, and documentation techniques, while the data analysis technique used in this study was qualitative descriptive analysis. The data sources in this study consist of primary and secondary data which are strengthened by the results of interviews with informants including; Village Head, Village Secretary, Deputy Village Consultative Body, Head of Planning and Hamlet Head. The results of this study indicate that the overall Management of the Village Revenue and Expenditure Budget (APBD) in Kasukia Village there are several indicators that are in accordance with the Minister of Home Affairs Regulation Number 113 of 2014 in the management of the Village Revenue and Expenditure Budget (APBD) and there is also one indicator that not maximal. This can be seen in the planning and implementation indicators, while the accountability indicators have not been maximized in terms of providing information to the community. as well as community participation support in managing the Village Revenue and Expenditure Budget (APBD).Keywords: Accountability, Management, Revenue and Expenditure Budget Village, Village Government.